Costs of Taxation and Benefits of Public Goods with Multiple Taxes and Goods - Anderson, James E. (2012)
The fact that raising taxes can increase taxed labor supply through income effects is frequently and erroneously used to justify greater public good provision than indicated by traditional, compensated analyses. We develop a model including multiple public goods and taxes and derive measures of the marginal benefits of public goods and the Marginal Cost of Funds (MCF) using both compensated and uncompensated measures. We confirm that the desirability of tax-financed public projects is independent of the method used. An important innovation is to show that the benefits of public goods must be adjusted by a benefit multiplier not previously seen in the literature if an uncompensated MCF is used.